2018
DOI: 10.3390/ma11060916
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Microtensile Bond Strength of a Polyetherketoneketone (PEKK) Tooth Post Cemented with Various Surface Treatments and Various Resin Cements

Abstract: The aim of this in-vitro research was to evaluate the microtensile bond strength in the newly introduced PEKK tooth post with various surface treatments and resin cements. A fiberglass tooth post was included in order to compare it with PEKK as a possible post material. The microtensile bond strengths of the fiberglass post (FRC Postec Plus) and the PEKK post (Pekkton®) were tested using three kinds of self-adhesive resin cements (G-CEM LinkAce, Multilink Speed, and RelyX U200) and one self-etching resin cemen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
20
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(29 citation statements)
references
References 35 publications
(45 reference statements)
1
20
0
Order By: Relevance
“…The shock absorbance with suitable strength (65 MPa) and fracture resistance properties of PEKK raises the possibility of using it as restorative material [19] , [20] . The PEKK has similar compression strength with a lesser modulus of elasticity compared to dentin [20] . Similar to PEEK, the elastic modulus of PEKK is comparable to those of bone.…”
Section: Properties Of Pekkmentioning
confidence: 99%
“…The shock absorbance with suitable strength (65 MPa) and fracture resistance properties of PEKK raises the possibility of using it as restorative material [19] , [20] . The PEKK has similar compression strength with a lesser modulus of elasticity compared to dentin [20] . Similar to PEEK, the elastic modulus of PEKK is comparable to those of bone.…”
Section: Properties Of Pekkmentioning
confidence: 99%
“…Similarly, Song et al reported higher tensile bond strength for sandblasted PEKK posts compared to the non pretreated ones. Moreover, silica coating did not have an additional effect on tensile bond strength coupled with sandblasting pretreatment for PEKK substrates [24]. However, these studies evaluated the bond strength of dental crowns and posts made of PEEK and PEKK but did not evaluate that of ball attachments used in tooth supported overdentures especially that debonding of commercially available ones are mentioned in the literature.…”
Section: Introductionmentioning
confidence: 99%
“…PEEK is more popular than PEKK both in field of scientific research and the real engineering as polymer matrix of composite. While, in addition to similar mechanical properties and crystalline behaviour to PEEK, PEKK received considerable attention because of its low price, low melting point and stable process, which results in better molding performance for PEKK composite and more applications 9 as compared to PEEK composite. However, PEKK is insulator, which limited its application in many fields, such as electronic engineering field.…”
Section: Introductionmentioning
confidence: 99%